Needleless graft preparation for anterior cruciate ligament reconstruction with 4-strand semitendinosus autograft: a biomechanical in vitro study using a porcine model - Peter Melcher; Stefan Schleifenbaum; Yasmin Youssef; Philipp Rolzhäuser; Pierre Hepp; Jan Theopold (BMC Musculoskeletal Disorders)
Abstract Background Ruptures of the anterior cruciate ligament (ACL) are common injuries. Reconstruction using autologous grafts is recommended to prevent further damage and functional impairment. Grafts are usually prepared with stabilizing sutures. The aim of this study was to evaluate if a 4-strand semitendinosus autograft preparation technique is non-inferior to conventional preparation techniques with regard to maximum tensile strength threshold. Methods Fresh porcine flexor tendons were used as specimens in this study. Four different preparation techniques for quadruple-folded tendons were compared. Group 1 three suture FiberWire® (n = 20) and Group 2 one suture FiberWire® (n = 20) using Krakow stitches, Group 3 (n = 10) using SPEEDTRAP® and piercing the autograft and 4 (n = 9) using SPEEDTRAP® without piercing the autograft for preparation. Biomechanical tensile testing included 50 sinusoidal cycles of preloading between 50 and 150 N at 1 Hz and load-to-failure was measured at 20 mm/min. Results Failure at the maximum load occurred at the filament for all samples, whereas failure of the suture/tendon interface was not observed. Load-to-failure was significantly higher in Group 1 (711 ± 91 N) than in all other groups. When comparing groups 2–4 load-to-failure was significantly higher in Group 2 (347 ± 24 N) than in Group 3 (258 ± 25 N, p < 0.02) but not than in Group 4 (325 ± 26N). Conclusion In all 4 Groups the load to failure was higher than the maximum tension force on the construct that will be applied by hand (182N). Therefore, the needleless preparation technique seems to be a valuable alternative to conventional techniques for the insertion of the graft into the joint during joint-near tibial fixation technique.